SCAPHOCEPHALY: A RETROSPECTIVE SERIES EXAMINING TREATMENT STRATEGIES AND LONG-TERM FOLLOW-UP - Micovic, Mirko; Bascarevic, Vladimir; Janicijevic, Aleksandar; Grujic, Jovan; Milic, Marina; Zivkovic, Bojana (Medical Research, 2025)
Introduction Scaphocephaly, the most common form of craniosynostosis, is caused by the premature fusion of the sagittal suture, resulting in an elongated skull shape and constrained cranial growth. Material and methods This retrospective study included all consecutive patients with sagittal synostosis who were operated on at the Clinic of Neurosurgery, UCCS, in the 20-year period. Detailed patient data were obtained from medical records and neuroradiological diagnostics. The follow-up period for these patients ranged from 6 to 20 years. The acquired data were thoroughly statistically analyzed. Results There were 93 children with a clear male preponderance. In the majority of children, there were no perinatal complications, and the majority of mothers didn’t have any chronic illnesses. Three types of surgical treatment were used, with an almost equal distribution. The mean blood loss during surgery varied across the three operative techniques, with the lowest blood loss observed using the TSEO technique. Successful treatment was observed in only 57.1% patients who underwent strip-suturectomy, 96.6% patients treated with the π procedure, and all patients treated with the TSEO technique. Statistical analysis revealed a significantly higher success rate of the TSEO and π procedure compared to strip-suturectomy. Cranial index remained dolichocephalic in 6/28 children treated with strip-suturectomy alone, while in all cases treated with TSEO and π procedure, cranial index normalized. The majority of operated children had no complications. Conclusion Successful treatment of scaphocephaly requires a case-specific approach that extends beyond the surgical procedure itself. This series emphasizes the need for individualized treatment plans and a multidisciplinary approach throughout the surgical process.